박람회 개최영향과 개최지지도의 관계: 지역애착의 조절효과를 중심으로 - 반가호(Jiahao Pan); 송운강(Woon-Gang Song); 유창리(Cangli Liu) (무역연구, 2024)
Purpose – This study aims to understand the impact of the development of an Expo on support for hosting said Expo from the perspective of residents, and to explore the moderating effect of regional affiliation on residents, so as to enrich the research results in the field of the impact of hosting the Expo. Design/Methodology/Approach – To conduct this research, a survey was conducted on residents affected by the Shouguang International Vegetable Technology Expo in Shandong, China in 2024, and 305 valid samples were used for analysis. Data reveals that positive economic, sociocultural, and environmental impacts, as well as negative environmental impacts, exert statistically significant influences on the degree of support for hosting the Expo. Findings – The outcomes of this study highlight that the positive and negative impacts of holding of the Expo on Shouguang community residents directly influence the degree of support for Expo development, with crucial modulatory roles played by community identification and community dependence within community attachment. Research Implications – The impacts of large-scale events on the host regions include increased tourism revenue, resident income, employment, government revenue, cultural cognition, and enhanced regional image. Therefore, studying the sustainability of the World Expo has far-reaching significance, not only for the tourism industry itself but also for the balanced development of the region. KCI Citation Count: 0